Assessing the Effect of Federal Universities Academics and National Youth Service Corps Members on the Conduct of General Elections in Nigeria - Kolawole, Aliyu M.; Ikedinma, Hope Amoge (Richtmann Publishing, 2021)
This study examined issues that necessitated the use of federal universities academics and national youth service corps members in the conduct of general elections in Nigeria and discussed the credibility of election management with their involvement. It also interrogated the effectiveness and challenges of using them by the Independent National Electoral Commission (INEC). The study utilised primary data that was collected through semi-structured interviews with thirty respondents. Secondary data was sourced from periodicals, journals, election manuals, and electoral act of 2010 as amended. The data collected were analysed using content analysis. The study showed that the need to sanitize the electoral system informed the use of universities academics and national youth service corps members. The study also showed that the academics and national youth service corps members have facilitated the credibility of the electoral system and that the activities of desperate politicians who are driven by the lust for political power are some of the challenges faced in using university academics and national youth service corps members. It is suggested that the current use of universities academics and national youth service corps members in the conduct of future elections should be sustained. Received: 5 August 2021 / Accepted: 30 september 2021 / Published: 5 November 2021